Israelis in the Gulf War in the light of a longitudinal analysis of morale - Levy, Shlomit (Psihološka obzorja (Ljubljana), 2006)
Distinction is made between three varieties of morale: cognitive, affective and instrumental. These three varieties have been systematically studied in Israel since 1967 by the Israel Institute of Applied Social Research. The population studied is Jewish adults residing in all localities of Israel (excluding kibbutzim). Israelis' behavior during the Gulf War is tested on the basis of the longitudinal analysis of varieties of morale. The Gulf War ischaracterized by increased optimism in the cognitive-perceptual mode and the affective mode (mood), along with the decline in coping ability. This coping problem is analyzed and discussed. The Gulf War did not produce any long-term changes in mood or coping ability, but has evoked a long-term cognitive impact by raising Israelis' awareness of the vulnerability of the home front.
Keywords: morala; morality; vojna; war; stres; psihologija; psychology; zalivska vojna; Israel; Izrael